Analisis Faktor-Faktor Yang Mempengaruhi Permintaan Bawang Merah Di Kelurahan Matawai Kecamatan Kota Waingapu - Alsyatry, Hifziah; Saragih, Elsa Christin; Mbana, Febyningsi Rambu Ladu (AGRI-SOSIOEKONOMI, 2024)
This study aims to understand the characteristics of shallots consumers and analyze the factors influencing shallots demand at Pasar Inpres Matawai, Waingapu City District. The research was conducted over two months, from June to July 2023. The study location is Matawai Village. Data on shallots demand was collected through observations at the research site where the community consumes shallots in Matawai Village and interviews using questionnaires with residents of Matawai Village who purchase and consume shallots at Pasar Inpres Matawai. The sampling technique used in this study is simple random sampling, which involves randomly selecting sample members from the population without considering the existing strata. A sample was then determined using Slovin’s formula with an error level of 10% (0.1), resulting in 91 household samples from Matawai Village. Data obtained from respondent interviews were processed and tabulated. The data were then analyzed using multiple linear regression analysis methods and described descriptively. The study findings on shallots consumer characteristics reveal that most consumers are of productive age, with an average age of 47 years. The education level of shallots consumers is generally high, with an average education level ranging from high school (SMA) to higher education. The majority of shallots purchasers are female, with the average occupation being housewives and an average family size of about 4 people. The variables of shallots and onion prices do not affect the demand for shallots, whereas the variables of income and family dependents do influence the demand for shallots.